Discussing reproductive goals with healthcare providers among women living with HIV in Canada: the role of provider gender and patient comfort. Issue 1 (1st January 2021) - Skerritt, Lashanda; de Pokomandy, Alexandra; O'Brien, Nadia; Sourial, Nadia; Burchell, Ann N; Bartlett, Gillian; Schuster, Tibor; Rouleau, Danielle; Proulx-Boucher, Karène; Pick, Neora; Money, Deborah; Gormley, Rebecca; et al.
Abstract: Antiretroviral therapy effectively prevents sexual and vertical transmission of HIV. Yet, some women living with HIV report having unmet needs for reproductive health care. This study measured the prevalence of women discussing reproductive goals with any current healthcare provider and assessed the effect of the current HIV care provider's gender on such discussions and whether comfort was a mediator. We analysed baseline and 18-month survey data from 533 women living with HIV enrolled in the Canadian HIV Women's Sexual and Reproductive Health Cohort Study (CHIWOS) (2013–2017), a community-based participatory study, restricting the analysis to participants aged 16–45 years. We used causal mediation analysis to estimate direct and indirect effects of the gender of one's HIV care provider on reproductive discussions, incorporating mediating and interaction effects of women having any provider with whom they felt comfortable discussing reproductive goals. Between the baseline and 18-month follow-up surveys, 34.3% (183/533) of women discussed their reproductive goals with a healthcare provider. Having a woman HIV care provider was associated with a 1.18 excess relative risk (ERR) of discussion (95%CI: 0.15, 2.20). The mediating effect of comfort was primarily explained by the fact that those participants with women providers felt more comfortable discussing their reproductive goals compared to participants with men providers, accounting for 66% (95%CI: 32%, 99%) of the total effect. Findings support that HIV provider gender affects women's comfort and whether they discuss reproductive goals, which must be acknowledged and addressed in care delivery.